Synthesis, characterization and Study of the physical properties of some new silicone polymers - Ahmed, Basma J.; Saleem, Maida H.; Tomma, Jumbad H. (Iraqi Journal of Science, 2025)
This study involves the synthesis of a new class of silicon polymers, designated as P1-P7, derived from dichlorodimethylsilane (DCDMS) in combination with various organic compounds (Schiff bases prepared from different amines and appropriate aldehydes or ketones) [I-V] through condensation polymerization. The structures of all monomers and polymers were characterization by FTIR and 1HNMR spectroscopy (for some polymers). The results of thermogravimetric analysis (TGA) and differential scanning calorimetry DSC test show stable thermal behaviour. Polymers with a higher concentration of aromatic rings in their repeating structural units exhibited a higher temperature for weight loss, indicating increased thermal stability. Thermal measurements reflect the fact that all the polymers prepared in this study possess thermal stability, and the most thermally stable are the polymers that contain more phenyl rings. The inhibitory feature of the prepared polymers is studied through many tests, which include measuring the erosion rate through methods known as weight loss and scanning electron microscopy tests. In the weight loss method, the inhibiter gives good efficiency in protecting aluminium metal, to reach the inhibition efficiency to 83% using polymer P5 inhibitor with concentration of 0.15 in 0.1 M solution of NaOH. On the other hand, P4 it showed the lowest inhibition efficiency of 16.74% at a concentration of 0.05. Scanning electron microscopy (SEM) images showed that a high corrosion inhibition efficiency of the polymers in NaOH solution (0.1 M), while the metal surface under the corrosion containing the inhibitors showed lower corrosion than that which could be found on the same metal surface, that is located in a completely empty media of the barrier and also clearly showed the protective layer on the surface. Viscosity testing in dimethylsulfoxide solvent showed that the true viscosity increases three fold when the concentration increases from 0.1 to 0.7. The results also showed that copolymer P7 has a higher viscosity.